Optimized multi-epitope neoantigen human cytomegalovirus vaccine based on adenovirus vectors elicits potent antiviral immunity - Jiang, Shasha; Zhang, Xianjuan; Zhao, Heping; Liu, Fengjun; Li, Zonghui; Yang, Xiaoli; Liu, Wenxuan; Lv, Jing; Zhang, Yi; Zhang, Yiran; Yu, Yan; Wang, Bin; et al. (Frontiers in Immunology, 2025)
IntroductionHuman cytomegalovirus (HCMV) induces severe morbidity and mortality in neonates, organ transplant recipients, and immunocompromised individuals. Currently, there is no licensed vaccine for HCMV. Given its ability to elicit a robust and enduring CD8 T cell response, we designed a recombinant adenovirus vaccine, referred to as the rAdMev vaccine, using bioinformatics methods based on human cytomegalovirus multi-antigen epitopes.MethodsFive proteins of HCMV (pp150, pp65, gB, gH, IE1) were analyzed using bioinformatics tools, and 58 T cell epitopes, 66 Th cell epitopes, and 15 B cell epitopes were screened out. The immunogenicity of the overlapping candidate peptides was initially tested in vitro using molecular docking techniques and flow cytometry. Subsequently, the selected dominant antigenic epitopes were recombined into the adenovirus vector. To enhance the vaccine’s efficacy, we employed a mixed priming schedule, combining an adenoviral vaccine with a protein vaccine. Finally, the immune response induced by heterologous vaccination was analyzed by proteomics.ResultsThe developed vaccine demonstrates favorable characteristics in terms of major histocompatibility complex affinity, immunogenicity, and population coverage. Primary immunization of mice with the rAdMev vaccine induces a potent innate immune response, characterized by highly activated dendritic cell subsets and the polarization of macrophages towards the M1 phenotype. Heterologous vaccination fosters the generation of robust polyfunctional (IFN-γ, TNF, IL-2, Granzyme B, Perforin) CD8 T cell responses, leading to the establishment of persistent effector memory T cells. Furthermore, we observed that heterologous vaccination activates fatty acid β-oxidation through the PPAR signaling pathway, enhancing mitochondrial biogenesis and promoting CD8 T cell memory formation in vivo.ConclusionsWe have developed a novel multi-epitope recombinant adenovirus vaccine that can elicit long-lasting antiviral cellular immunity, providing new insights into the development of vaccines against HCMV.